CULTURAL ASPECTS OF IMMEDIACY IN AN ASIAN CLASSROOM CONTEXT - López-Ozieblo, Renia (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Among the various factors affecting students’ learning, immediacy is probably the one that has been most studied over the last four decades. Immediacy, a term coined by Mehrabian (1967), refers to verbal and nonverbal behaviours used by interlocutors to decrease physical and physiological distance between them, thus creating affinity, liking and affect. However, a number of questions arise as to the suitability of the various immediacy scales and their cultural significance in a non U.S. context, such as Hong Kong. Furthermore we were interested in possible differences in teachers’ perception based on students’ motivation. This paper presents the first part of an immediacy study, based on students of the Department of English of the Hong Kong Polytechnic University (looking into mapping patterns of behaviours that increase immediacy). The results indicate that Hong Kong students prefer the holistic approach of the Chinese traditional teacher, a teacher who goes beyond just teaching in class, and that nonverbal actions are not high in their list of preferred behaviours in teachers, such as gestures, walking around the classroom or standing close to students (unlike what has been observed among U.S. students). Resumen Entre los diversos factores que afectan el aprendizaje de los estudiantes, la inmediatez es probablemente el que más se ha estudiado en las últimas cuatro décadas. La inmediatez, un término acuñado por Mehrabian (1967), se refiere a los comportamientos verbales y no verbales utilizados por los interlocutores para disminuir la distancia física y fisiológica entre ellos, creando así afinidad, y afecto entre ellos. Sin embargo, la literatura plantea una serie de dudas en cuanto a la idoneidad de las distintas escalas de inmediatez y su importancia cultural en un contexto no estadounidense, tal como el de Hong Kong. Este estudio buscaba también investigar las posibles diferencias en la percepción que los estudiantes tienen de los docentes según su motivación. Este trabajo presenta la primera parte de un estudio de inmediatez entre estudiantes del Departamento de Inglés de la Universidad Politécnica de Hong Kong (buscando patrones en el comportamiento de profesores que aumenten inmediatez en el aula). Los resultados indican que los estudiantes de Hong Kong prefieren profesores que van más allá de la enseñanza en el aula, desarrollando un enfoque holístico, típico de profesores del sistema educativo tradicional chino, y que las acciones no verbales, como gestos, pasearse por el aula o acercarse a los estudiantes (importantes para estudiantes de Estados Unidos), no son comportamientos tan importantes para el alumno de Hong Kong.